An improved project management for interior design practice / Nur Maizura Ahmad Noorhani - Ahmad Noorhani, Nur Maizura (2016)
The competencies of interior designers managing construction projects, particularly in project management have frequently been questioned. Central to this argument is the claim that the interior designer competencies, which was developed through education and practice tend to be very biased on design skills and knowledge at the expanse of project management. To date, there has been little research to justify the validity of the argument. In seeking to address this argument, this research was undertaken to establish to what extent is project management neglected in the academic and practice of interior design, and if so, where are the gaps. A mixed method research method was employed for the research. A quantitative research method with seventy-eight respondents was first adopted to establish the validity and extent to which project management was lacking in interior design practice. This was followed with a qualitative research method to identify precisely where the gap in project management education and interior design practice exists. To identify the gaps, fourteen key respondents were selected for interviews during the data collection. This was triangulated with content analysis method, which critically analyses the interior design syllabus offered by four leading local higher institutions. Activities undertaken by the interior design professional associations were also analysed. The findings found significant gaps in learning project management in the interior design higher education and interior design practice. The most important solutions to bridge the gaps is to improve the project management competencies of interior designers through education and practice were identified and suggested. To aid a holistic conceptualization of the project management skills and knowledge for the developmement of their competencies which can be added to the interior design education and practice, a framework was proposed. Significant new knowledge relating to interior design competencies was identifed through this research. This encompases the identification of the actual project management skills and knowledge required to improve the current interior design education curriculum offered by higher education. The skills and knowledge required in practice which should be promoted by the interior design professional associations was also identified. Notwithstanding, more research is suggested to follow through with this framework to structure and improve interior design curriculum in higher education. Research on how the project management skills and knowledge can be incorporated into the interior design continuing professional development program (CPD) can also be introduced.